Optimal capacity allocation method of integrated energy system considering renewable energy uncertainty - Xue, Yuantian; Zhang, Cheng; Jiang, Fan; Dou, Wu; Zhang, Hongtian; Yang, Chenlai (Frontiers in Energy Research, 2022)
With the reduction of fossil energy and the increase of energy consumption, the development and utilization of new energy is an inevitable trend. Renewable energy has attracted attention because of its cleanness and abundance. However, affected by the randomness and intermittence of renewable energy, it is difficult for the traditional power system to meet the needs of users after renewable energy is connected, and it is difficult to solve the consumption problem of renewable energy by relying on the traditional power system alone. To address this problem, an integrated energy system (IES) is constructed using a two-layer optimization method for the operation strategy and capacity allocation of the integrated energy system, and a particle swarm optimization algorithm is used to solve the multi-objective problem, taking renewable energy consumption, operation cost, and investment cost as the optimization indexes, and considering the equipment operation characteristics, uncertainty of renewable energy and the model constraints. The optimization results obtained from the solution are compared with the traditional energy supply system, and it is verified that the proposed method can achieve the lowest cost investment in the system while satisfying the reliability and safety constraints.